1998
DOI: 10.1093/ajcn/68.2.226
|View full text |Cite
|
Sign up to set email alerts
|

Influence of medium-chain and long-chain triacylglycerols on the control of food intake in men

Abstract: Hunger may be delayed and food intake reduced under metabolic conditions that spare carbohydrate oxidation, especially during oxidation of medium-chain triacylglycerols (MCTs) or monounsaturated triacylglycerols. In 12 healthy, adult, male volunteers isolated and deprived of any time cues, we compared the effects of 4 high-carbohydrate breakfasts (1670 kJ) supplemented either with a fat substitute (Sub; 70 kJ) or with 1460 kJ fat as monounsaturated long-chain triacylglycerols (LCT-U), saturated long-chain tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
63
5
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 49 publications
6
63
5
1
Order By: Relevance
“…Furthermore, different physicochemical properties of fats could influence their satiating properties. These include fatty acid chain length (Bach et al, 1996;Stubbs & Harbon, 1996;Van Wymelbeke et al, 1998), degree of fatty acid unsaturation (Shimomura et al, 1990;Lawton et al, 1997;Kamphuis et al, 2001), degree of emulsification (Welch et al, 1985(Welch et al, , 1988 and emulsion stability (Armand et al, 1992). In this context it has recently been shown that a fat emulsion (Olibra TM ) formulated from palm oil and oat oil fractions significantly decreased energy and macronutrient intakes in lean, overweight and obese subjects up to 36 h post-consumption (Burns et al, 2000(Burns et al, , 2001.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, different physicochemical properties of fats could influence their satiating properties. These include fatty acid chain length (Bach et al, 1996;Stubbs & Harbon, 1996;Van Wymelbeke et al, 1998), degree of fatty acid unsaturation (Shimomura et al, 1990;Lawton et al, 1997;Kamphuis et al, 2001), degree of emulsification (Welch et al, 1985(Welch et al, , 1988 and emulsion stability (Armand et al, 1992). In this context it has recently been shown that a fat emulsion (Olibra TM ) formulated from palm oil and oat oil fractions significantly decreased energy and macronutrient intakes in lean, overweight and obese subjects up to 36 h post-consumption (Burns et al, 2000(Burns et al, , 2001.…”
Section: Introductionmentioning
confidence: 99%
“…For example, medium-chain triacylglycerols appear to increase satiety and decrease energy intake to a greater extent than long chain triacylglycerols. 5,6 Furthermore, in normal weight men and in obese men, 7 fats infused into the small intestine in the form of triacylglycerol emulsion have been shown to suppress short-term hunger ratings and food intake to a greater extent than an isoenergetic infusion of carbohydrate.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, MCTs may contribute to spontaneous energy-intake reduction and greater weight loss than LCTs (13). For example, the addition of 38 g of fat as monounsaturated LCTs, saturated LCTs, or MCTs to high-carbohydrate breakfasts delayed the request for subsequent FI compared with the low-fat breakfast in healthy adults (14). Furthermore, both high-LCT breakfasts led to the highest energy intake at lunch and dinner, but it was the MCT breakfast that resulted in the lowest FI, suggesting that, despite the high energy density of high-fat meals, the high-MCT diet enhances satiation and the suppression of FI.…”
Section: Fats (Lipids)mentioning
confidence: 99%